Clinical Application of Partial Splenic Embolization - Yong-Song Guan; Ying Hu (The Scientific World Journal)
Partial splenic embolization (PSE) is one of the intra-arterial therapeutic approaches of diseases. With the development of interventional radiology, the applications of PSE in clinical practice are greatly extended, while various materials are developed for embolization use. Common indications of PSE include hypersplenism with portal hypertension, hereditary spherocytosis, thalassemia, autoimmune hemolytic anemia, splenic trauma, idiopathic thrombocytopenic purpura, splenic hemangioma, and liver cancer. It is also performed to exclude splenic artery aneurysms from the parent vessel lumen and prevent aneurysm rupture, to treat splenic artery steal syndrome and improve liver perfusion in liver transplant recipients, and to administer targeted treatment to areas of neoplastic disease in the splenic parenchyma. Indicators of the therapeutic effect evaluation of PSE comprise blood routine test, changes in hemodynamics and in splenic volume. Major complications of PSE include the pulmonary complications, severe infection, damages of renal and liver function, and portal vein thrombosis. The limitations of PSE exist mainly in the difficulties in selecting the arteries to embolize and in evaluating the embolized volume.